1979
DOI: 10.4319/lo.1979.24.6.1154
|View full text |Cite
|
Sign up to set email alerts
|

Acidification and other chemical changes Halifax County lakes after 21 years

Abstract: Sixteen of 23 lakes sampled in 1955 show no sign of significant physical alterations within their drainage basins over a 21‐year interval, so that chemical changes in these lakes can be assumed to reflect changes in atmospheric inputs. In all 16, the pH levels have declined, with greater declines in the higher pH (near neutrality) lakes. After correction for sea‐salt input, concentrations of sodium, magnesium, calcium, potassium, and sulfate show no significant change. Sulfate and hydrogen ions are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…1933 to 1944 this part of the Newfoundland's island was receiving acid precipitation at pH values above 4.5. This observation is in accordance with Watt et al, (1979), who reported no apparent increase in Ca and Mg content in Nova Scotia lakes, which had undergone a significant pH decline over a 21 year period (1955 to 1977). Martin & Brydges (1986), in reviewing long term trends in sulfur emissions in North America, have reported increasing deposition over the 1950's and 1960's to reach a maximum level in the early 1970's, with declining deposition since the mid 1970's.…”
Section: Atmospheric Deposition -Geochemistrysupporting
confidence: 80%
“…1933 to 1944 this part of the Newfoundland's island was receiving acid precipitation at pH values above 4.5. This observation is in accordance with Watt et al, (1979), who reported no apparent increase in Ca and Mg content in Nova Scotia lakes, which had undergone a significant pH decline over a 21 year period (1955 to 1977). Martin & Brydges (1986), in reviewing long term trends in sulfur emissions in North America, have reported increasing deposition over the 1950's and 1960's to reach a maximum level in the early 1970's, with declining deposition since the mid 1970's.…”
Section: Atmospheric Deposition -Geochemistrysupporting
confidence: 80%
“…Marine aerosols generated by ocean waves are deposited over terrestrial catchments in Atlantic Canada and elsewhere and contribute ions to drainage waters (Watt et al 1979;Farrell et al 1998). The ionic composition of the marine aerosols has been measured, and is consistent with that in seawater (Junge 1972), so that in assessing marine influence, Cl -measured in freshwaters can be generally used as a quantitative indicator of marine ionic contribution.…”
Section: Seasalt Influence On Freshwater Chemistrymentioning
confidence: 98%
“…Shaw (1979) showed that Atlantic Canada, the eastern-most part of the North American continent, received low, but measurable acid deposition originating mostly in central Canada, the Ohio Valley and the eastern seaboard of the United States. Later studies by Watt et al (1979Watt et al ( , 1983 and Kerekes et al (1982) showed that some surface waters were very acidic in the region, and that deleterious effects to aquatic ecosystems from acid rain could be measured. The main objectives of aquatic chemistry research in the early part of the 1980s were to (a) follow up on the earlier work of Gorham (1957) and Hayes and Anthony (1958) to better understand how water chemistry in the region differed from that of other regions in North America and Europe, (b) delineate the spatial extent of acidification effects in Atlantic Canada, and (c) assess long-term and seasonal trends in water chemistry to see if changes attributable to acid rain could be detected.…”
Section: Introductionmentioning
confidence: 97%
“…A complication in assessing ∆ANC (poll) in the two streams is that the sea-salt-correction occasionally produces negative values of Na + during winter episodes. Assuming that the sea-salt-correction of major chemical constituents should be in equal proportions to sea water (Watt et al, 1979; …”
Section: Model Uncertaintymentioning
confidence: 99%
“…Water samples were analysed for major ions, dissolved organic carbon (DOC), and nitrate at an Environment Canada's laboratory in Moncton, New Brunswick (Table 1). Sea-salt-correction was made for all major ions, using ion to chloride ratios (SO (Watt et al, 1979) and assuming that all chloride is of marine origin.…”
Section: Study Areamentioning
confidence: 99%